The productivity effects of worker mobility between heterogeneous firms - Bastian Stockinger; Katja Wolf (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
Several empirical studies find that worker inflows from more productive or otherwise superior firms increase hiring firms' productivity. We conduct a similar analysis for Germany, using a unique linked employer-employee data set, and ranking sending and hiring establishments by their median wage. We find that inflows from superior (higher-paying) establishments do not increase hiring establishments' productivity, but inflows from inferior establishments seem to. Further analyses suggest this effect is due to positive selectivity of such inflows from their sending establishments. Our findings can be interpreted as evidence of a reallocation process by which the best employees of lower-paying establishments become hired by higher-paying establishments. This process reflects the increasingly assortative pattern of worker mobility in Germany, to which our findings suggest a micro-foundation at the establishment and worker levels. – – Empirische Studien zeigen, dass Zugänge von Beschäftigten aus produktiveren Betrieben die Produktivität der einstellenden Betriebe steigern. Wir untersuchen diesen Zusammenhang für Deutschland anhand eines eigens generierten Linked Employer-Employee Datensatzes. Dabei ordnen wir Herkunfts- und Zielbetriebe von Betriebswechslern anhand ihres Medianlohns. Unsere Ergebnisse zeigen, dass Beschäftigtenzugänge aus höher entlohnenden Betrieben keine Wirkung auf die Produktivität der Zielbetriebe haben. Zugänge aus geringer entlohnenden Betrieben hingegen haben unseren Ergebnissen zufolge einen positiven Produktivitätseffekt. Weitere Analysen ergeben, dass dieser Effekt in einer Positivauswahl dieser Beschäftigten aus ihren Herkunftsbetrieben begründet liegt. Ein Teil der produktivsten Beschäftigten von Betrieben mit niedrigerem Lohnniveau wechselt also zu Betrieben mit höherem Lohnniveau. Dieser Prozess spiegelt ein bereits bekanntes Muster der Beschäftigtenmobilität in Deutschland wider, wonach sich hochbezahlte Beschäftigte zunehmend in hoch entlohnende Betriebe sortieren. Unsere Ergebnisse können daher als Mikro-Fundierung für dieses gesamtwirtschaftliche Muster dienen.
Keywords: D24; J61; J62; R23; 330; Knowledge Spillovers; Labor Mobility; Plant-Level Productivity